A Note on the Adversary Degree Associated Reconstruction Number of Graphs. (31st March 2013) - Monikandan, S.; Sundar Raj, S.; Jayasekaran, C.; Santhakumaran, A. P.
Abstract : A vertex-deleted subgraph of a graph G is called a card of G . A card of G with which the degree of the deleted vertex is also given is called a degree associated card (or dacard) of G . The degree associated reconstruction number drn (G ) of a graph G is the size of the smallest collection of dacards of G that uniquely determines G . The adversary degree associated reconstruction number of a graph G, adrn (G ), is the minimum number k such that every collection of k dacards of G that uniquely determines G . In this paper, we show that adrn of wheels and complete bipartite graphs on at least 4 vertices is 2 or 3.